Vacuum Switching Technology for Future of Power Systems. (June 2022) - Yao, Xiaofei; Wang, Jianhua; Ai, Shaogui; Liu, Zhiyuan; Geng, Yingsan; Hao, Zhiguo
Graphical abstract: Highlights: China pledged to achieve carbon neutrality in 2060 at COP21. Vacuum is a preferred alternative to SF6 in switching in future power systems. Fast vacuum circuit breaker can interrupt a fault current in the first half-cycle. Fast vacuum switching technology is promising for accurate controlled switching. Future power systems could benefit from the application of fast vacuum switches. Vacuum switching technology is changing the future of power systems. Abstract: Even though switching in vacuum is a technology with almost 100 years of history, its recent developments are still changing the future of power transmission and distribution systems. First, current switching in vacuum is an eco-friendly technology compared to switching in SF6 gas, which is the strongest greenhouse gas according to the Kyoto Protocol. Vacuum, an eco-friendly natural medium, is promising for reducing the usage of SF6 gas in current switching in transmission voltage. Second, switching in vacuum achieves faster current interruption than existing alternating current (AC) switching technologies. A vacuum circuit breaker (VCB) that uses an electromagnetic repulsion actuator is able to achieve a theoretical limit of AC interruption, which can interrupt a short-circuit current in the first half-cycle of a fault current, compared to the more common three cycles for existing current switching technologies. This can thus greatly enhance the transient stability of power networks in the presence of short-circuit faults, especially for ultra- and extra-high-voltage power transmission lines. Third, based on fast vacuum switching technology, various brilliant applications emerge, which are benefiting the power systems. They include the applications in the fields of direct current (DC) circuit breakers (CBs), fault current limiting, power quality improvement, generator CBs, and so forth. Fast vacuum switching technology is promising for controlled switching technology in power systems because it has low variation in terms of opening and closing times. With this controlled switching, vacuum switching technology may change the "gene" of power systems, by which power switching transients will become smoother.